PLTD Engine Tank Oil Volume Monitoring System using HC-SR04 Ultrasonic Sensor Based on Internet of Things (IoT) - Prayetno, Eko; Nadapdap, Trisianto; Susanti, Ani Sari; Miranda, Delta (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
The Diesel Power Plant is an oil-fired generator. The PLTD engine in Ranai uses Bio Solar fuel to produce 1 MW (MegaWatt) of power. The PLTD engine in Ranai each has one tank with a capacity of 1820 liters. Within 1 hour of using a machine with a power of ±, 750 KW (Kilo Watt) can consume ± 182 liters of oil. The IoT system serves to simplify the work in the oil distribution system. This IoT system uses the ESP8266 as a microcontroller, the HC-SR04 ultrasonic sensor as a volume level reader for the oil in the engine tank, and a relay as a replacement switch pump on or off. This tool works in real-time to help reduce the risk of negligence in refueling the engine. The Device testing results showed good results because the error value in the measurement distance test was 0%. The tool can provide fast and accurate information because it is equipped with an information system using Android and notifications from email messages.